2007
DOI: 10.1097/ta.0b013e31815202c9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Controlled Fluid Resuscitation in the Treatment of Severe and Uncontrolled Hemorrhagic Shock

Abstract: In severe and uncontrolled hemorrhagic shock, some fluid must be given in proper time to improve tissue perfusion and avoid early death. Among three fluid resuscitation methods, controlled fluid resuscitation can effectively decrease additional blood loss, avoid excessive hemodilution and coagulopathy, improve the early survival rate, and reduce the apoptosis of visceral organs in rats with severe and uncontrolled hemorrhagic shock. This model supports the concept that when surgical care is not readily availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
2
25
0
1
Order By: Relevance
“…We have recently seen similar changes in adipokines in patients with severe burns [16]. These adipokines have been suggested to play important roles in tissue inflammation; however, a role in critically ill patients has yet to be elucidated [51-53]. In the present study, reduced adipokine levels were observed in the presence of injury rather than disuse, suggesting a greater influence of the injury component.…”
Section: Discussionsupporting
confidence: 74%
“…We have recently seen similar changes in adipokines in patients with severe burns [16]. These adipokines have been suggested to play important roles in tissue inflammation; however, a role in critically ill patients has yet to be elucidated [51-53]. In the present study, reduced adipokine levels were observed in the presence of injury rather than disuse, suggesting a greater influence of the injury component.…”
Section: Discussionsupporting
confidence: 74%
“…All the rats suffered approximately 50% blood loss based on their body weight and survived in all the above-mentioned three phases. These results are consistent with our previous studies which reported that rats could survive acute blood loss to 50% 2007a;2007b). Fig.1 shows MAP changes of the rats in the three groups.…”
Section: Characteristics Of the Animal Modelsupporting
confidence: 82%
“…Volume expansion with crystalloid (hypertonic saline, ringer's lactate, normal saline) or synthetic colloid solutions play an even more important role in bleeding patients when blood products are not an option. Hypotensive resuscitation of these patients should also be considered until definitive control of the bleeding is achieved [8,9]. Acute normovolemic hemodilution may prove to be a valuable means by which to reduce intraoperative blood loss [10,11], provided an adequate beginning Hb level is present for the effective employment of this technique.…”
Section: Discussionmentioning
confidence: 99%